Multi-objective approach to forecast design refresh time due to COTS obsolescence - BULKAN, SEROL (My University, 2022)
The purpose of this study is to provide program managers and systems engineers with a novel algorithm in determining the design refresh time (DRT) of sustainment-dominated systems due to COTS obsolescence. Most of the research done so far has focused on cost optimization. The main contribution of the study is two-fold. First, besides cost optimization, we have introduced efficiency optimization within a balanced approach to determine the DRT, under multiple objectives. Second, we used a set-based approach over the hypervolume quality values of solutions rather than population-based Pareto solutions. We proposed a discrete-time simulation model by using Multi-Objective Evolutionary Algorithms where the deterioration over the quality values of Pareto solution sets is used as an indicator for a DRT. We supported the proposed mathematical model in theory with empirical findings from a case study for a sustainment-dominated Naval Command and Control System that was designed in 2004 and deployed in 2007. We ran the simulation as for 2007 and conducted an analysis over the cost and operational efficiency objectives to compare the situation experienced in real life against the simulation outputs of the proposed model. The results revealed that not only the total life cycle cost but also efficient operational sustainability of a system would be increased significantly if the system had gone through design refreshes as proposed by the model. We showed that the deterioration of the Pareto optimal solutions\" hypervolume quality values over time is an effective marker to decide the optimal DRT under conflicting multiple objectives.
Keywords: Sosyal ve Beşeri Bilimler; Ekonometri; Yöneylem; Endüstri Mühendisliği; Mühendislik ve Teknoloji; Social Sciences and Humanities; Econometrics; Operational Research; Industrial Engineering; Engineering and Technology; MÜHENDİSLİK, ENDÜSTRİYEL; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); OPERASYON ARAŞTIRMA VE YÖNETİM BİLİMİ; Ekonomi ve İş; Sosyal Bilimler (SOC); ENGINEERING, INDUSTRIAL; ENGINEERING; Engineering, Computing & Technology (ENG); OPERATIONS RESEARCH & MANAGEMENT SCIENCE; ECONOMICS & BUSINESS; Social Sciences (SOC); Management Science and Operations Research; Organizational Behavior and Human Resource Management; General Engineering; Engineering (miscellaneous); Social Sciences & Humanities; Physical Sciences; COTS obsolescence; design refresh time; DMSMS; MOEA; set based hypervolume; SOFTWARE OBSOLESCENCE; REPLACEMENT DECISIONS; INVENTORY MODEL; SYSTEM; FRAMEWORK; IMPACT; SKILLS